PENERAPAN BUDIDAYA PADI ORGANIK UNTUK MENGHASILKAN PANGAN YANG SEHAT DAN KEBERLANJUTAN USAHA TANI - Toana, Moh. Hibban; Mile, Yuldi; Pasaru, Flora; Khasanah, Nur; Haji Nasir, Burhanuddin (Jurnal Abdi Insani, 2024)
Organic rice cultivation is a way of growing rice without using inorganic fertilizers and synthetic chemical pesticides. The fertilizer used is organic fertilizer and pest and disease control is carried out using the concept of integrated pest control. The "Tunas Harapan" farmer group, Sejahtera Village, Palolo District, Sigi Regency, with 20 members, is one of the farmer groups active in rice farming activities. The partners' problems in promoting organic rice cultivation are: not being able to prepare organic fertilizer and non-chemical pesticides as needed, and the low productivity of the rice produced. The community service program aims to assist partner farmers in preparing organic production facilities in the form of developing organic fertilizer, developing synthetic non-chemical pesticides made from local raw materials, and improving rice cultivation technology based on organic farming. The method applied is training and technology demonstration. The results of community service show that partners know the techniques for developing local microorganisms as liquid organic fertilizer and utilizing plants that have insecticidal properties as botanical pesticides. The application of liquid organic fertilizer in the organic rice cultivation demonstration plot showed better plant growth compared to without the application of liquid organic fertilizer. The knowledge and skills of participants in implementing organic rice cultivation increased to 45% of farmers who really understand organic rice cultivation technology.